An appraisal of the situation of palliative care in Poland in 2018 - Ciałkowska-Rysz, Aleksandra (Medycyna Paliatywna/Palliative Medicine, 2019)
The situation of, and accessibility to, palliative care in 2018 was assessed in this paper. The data used in this study are from the websites of the national central and regional divisions of the National Health Fund, the Ministry of Health, the Education Centre for Nurses and Midwives, the Medical Examination Centre, and from the map of healthcare needs in 2019 and the Central Statistical Office. This study demonstrated that access to palliative and hospice care services in Poland was territorially differentiated. Disproportions between voivodeships concern the number of units, the availability of individual services, access to specialist staff, and expenditure on palliative care services per inhabitant of the voivodeship. The availability of home services was the highest, while access to outpatient services was the worst. Coordinated actions of state institutions are required in order to systematically improve legal guaranteed access to palliative care services.